Policy Analysis of Amendments to the KPK Law in the Eradication of Corruption in Indonesia - Andes Robensyah (PT Justitia Legal Research, 2025)
The amendment of Law Number 30 of 2002 concerning the Corruption Eradication Commission through Law Number 19 of 2019 became a turning point in the institutional weakening of anti-corruption institutions in Indonesia. The revision caused widespread controversy because it was considered to shift the character of the KPK from an independent state institution to part of the executive power cluster. This study aims to analyze the direction of government policies in amending the KPK Law and assess its implications on the effectiveness of eradicating corruption. The method used is normative legal research with a legislative and conceptual approach, through the examination of legal norms, doctrines, and academic views. The results of the study show that the revision of the KPK Law presents a number of strategic restrictions, including the establishment of a Supervisory Board with technical authority, restrictions on wiretapping authority, the granting of the authority to terminate cases, and the change in the status of KPK employees to state civil servants. These changes systematically narrow the KPK's space for movement, erode its functional independence, and open up space for political power intervention in the enforcement of corruption laws. The policy direction of the revision of the KPK Law does not reflect the strengthening of the corruption eradication system, but rather shows the tendency of domestication and power control over the KPK, which has the potential to weaken public trust and the effectiveness of corruption eradication in Indonesia.